Filarial infections in lemurs: evidence for a wide geographical distribution and low host specificity among lemur species - Kiene, Frederik; Springer, Andrea; Andriatsitohaina, Bertrand; Ramsay, Malcolm S.; Rakotondravony, Romule; Strube, Christina; Radespiel, Ute (American Journal of Primatology, 2023)
The relevance of emerging infectious diseases continues to grow worldwide as human activities increasingly extend into formerly remote natural areas. This is particularly noticeable on the island of Madagascar. As closest relatives to humans on the island, lemurs are of particular relevance as a potential origin of zoonotic pathogen spillover. Knowledge of pathogens circulating in lemur populations is, however, very poor. Particularly little is known about lemur hemoparasites. To infer host range, ecological and geographic spread of the recently described hemoparasitic nematode Lemurfilaria lemuris in northwestern Madagascar, a total of 942 individuals of two mouse lemur species (Microcebus murinus [n = 207] and Microcebus ravelobensis [n = 433]) and two rodent species (the endemic Eliurus myoxinus [n = 118] and the invasive Rattus rattus [n = 184]) were captured in two fragmented forest landscapes (Ankarafantsika National Park and Mariarano Classified Forest) in northwestern Madagascar for blood sample examination. No protozoan hemoparasites were detected by microscopic blood smear screening. Microfilaria were present in 1.0% (2/207) of M. murinus and 2.1% (9/433) of M. ravelobensis blood samples but not in rodent samples. Internal transcribed spacer 1 (ITS-1) sequences were identical to an unnamed Onchocercidae species previously described to infect a larger lemur species, Propithecus verreauxi, about 650 km further south. In contrast to expectations, L. lemuris was not detected. The finding of a pathogen in a distantly related host species, at a considerable geographic distance from the location of its original detection, instead of a microfilaria species previously described for one of the studied host species in the same region, illustrates our low level of knowledge of lemur hemoparasites, their host ranges, distribution, modes of transmission, and their zoonotic potential. Our findings shall stimulate new research that will be of relevance for both conservation medicine and human epidemiology.